MEMAHAMI POLITIK MASYARAKAT MUSLIM - M Firdaus Khalimi (Jurnal Dialog, 2017)
Politics movement is a reaction of social changes. Hence, all of parties (including Islamic Parties) must understand the characteristics and structures of society (social structures usually are based on job, education, income, asset and religion). Modern society tends to pragmatism (demanding political aspiration as their appetite). One of failure of Islamic parties was the lack of understanding social structure of muslim society. This article highlights the importance of understanding the structure of muslim society for Islamic parties to do self, idea and movement contextualization.